"Indian" strains of Trichophyton mentagrophytes with reduced itraconazole susceptibility in Germany. (1st December 2021) - Brasch, Jochen; Gräser, Yvonne; Beck‐Jendroscheck, Vera; Voss, Karen; Torz, Kaspar; Walther, Grit; Schwarz, Thomas
Summary: We use published reports and three of our own tinea cases as an opportunity to report on "Indian" strains of Trichophyton (T.) mentagrophytes with ITS genotype VIII and reduced susceptibility to itraconazole due to the mutation c.1342G>A in the SQLE gene in Germany. In vitro measurements of resistance revealed normal susceptibility to terbinafine, but markedly reduced susceptibility to itraconazole – although no valid breakpoints are currently defined and minimum inhibitory concentrations (MICs) depend on the methods used. Problems related to the determination and interpretation of MICs are outlined. Our cases show that azole‐resistant "Indian" strains of T. mentagrophytes with ITS genotype VIII occurred in Germany as early as 2011, which is earlier than was previously assumed. This variant of the pathogen cannot be phenotypically distinguished from customary strains of T. mentagrophytes ; its identification is based on genetics. The taxonomic classification is still under debate. This variant is anthropophilic and causes only mildly inflammatory tinea lesions with many fungal elements. Its further dissemination must therefore be expected. Prerequisites for rapid and valid antimycotic testing against dermatophytes need to be developed.